Train future teachers for sociopolitical action in the context of science education - Linhares, Elisabete Fernandes (2018)
Education in general and, more specifically, the training of teachers should provide opportunities for students to develop skills to intervene responsibly and critically in solving society's problems, in particular through targeted teaching practices for responsible citizenship. This study aimed to understand the impact of activism initiatives in future teachers and identify difficulties and potential associated with this type of activities. This research on own professional practice, focuses thus on the analysis of narratives developed by prospective teachers attending an Environment discipline of the 2nd year of the Degree in Basic Education from a Higher School of Education in Portugal, after having performed activism initiatives with different publics. The results point to the existence of some difficulties. But, essentially, relate to an educative experience that provided significant learning, guided by a constant engagement and increasing motivation in developed activism projects.